Effects of tourism development on economic growth: An empirical study of China based on both static and dynamic spatial Durbin models - Honghong Liu; Ye Xiao; Bin Wang; Dianting Wu (SAGE Journals, 2021)
This study applies the dynamic spatial Durbin model (SDM) to explore the direct and spillover effects of tourism development on economic growth from the perspective of domestic and inbound tourism. The results are compared with those from the static SDM. The results support the tourism-led-economic-growth hypothesis in China. Specifically, domestic tourism and inbound tourism play a significant role in stimulating local economic growth. However, the spatial spillover effect is limited to domestic tourism, and the spatial spillover effect of inbound tourism is not significant. Furthermore, the long-term effects are much greater than the short-term impact for both domestic and inbound tourism. Plausible explanations of these results are provided and policy implications are drawn.
Keywords: Economics; Hospitality Management